Profile of Internal Injuries to Thorax, Abdomen and Pelvis Sustained by the Victim During Fatal Road Traffic Accident in Central India (Medico Legal Update, 2019)
Road traffic accident is a complex phenomenon. Constant rise in the number of motor vehicles, rampant encroachment of road, easy to avail the vehicle because of loan facility, nasty tendency of violating traffic rules and anarchic traffic systems have greatly contributed to rapid increase in RTAs. Population explosion is a catalyzing factor for a number of accidents. The rise of road traffic accidents has become a major public health problem. The injuries, disability and fatality resulting from unexpected RTAs put a significant drain on the economy of the nation. The present study was a cross-sectional study conducted in central India during 1.6 year period from 1st June 2014 to 1st Jan 2017. During the study period, a total of 757 medicolegal autopsies were conducted in this institute, out of which 109 cases of fatal road traffic accidents (died on spot or within 24 hours of accident) were studied. The purpose of the study was to know the pattern of injuries in victims of fatal RTAs and to establish the correlation between the injury and the cause of death.